0302 The Daily Rhythm Of Human Physiological Sleepiness In Response To 40 H Continuous Wakefulness Remains Unchanged Following Brain Insult. (27th April 2018) - Campbell, C; Adewale, F; Grillakis, A; Capaldi, V; Mantua, J; Brager, A; Yarnell, A
Abstract: Introduction: Daytime sleepiness and nighttime sleep disturbance are commonly reported in mild traumatic brain injury (mTBI) patients. This suggests a difference in the accumulation and dissipation of sleep pressure between concussed and non-concussed patients. It is unknown whether or not these symptoms persist beyond 3 months post-injury. We sought to measure changes in physiological sleepiness 3 -12 months post-injury, expecting injured volunteers to exhibit increased sensitivity to acute, total sleep deprivation (40 h; n=13; 6 concussed; 25 yo). Methods: At-home actigraphic sleep (2 wk) was ~ 8 h at baseline. After laboratory acclimation, the volunteers underwent 40 h of forced wakefulness followed by an 8 h sleep opportunity (recovery). A 20-minute Maintenance of Wakefulness Test (MWT) was used to objectively assess physiological sleepiness by measure of sleep latency. The test was performed every 4 hours for the duration of forced wakefulness and the recovery period, amounting to 12 scored MWTs. Results: Rates of accumulated sleepiness across the 40 h of forced wakefulness were similar for concussed subjects and age-matched controls (p=0.161). Rates of dissipated sleepiness across the recovery period were also similar for concussed subjects and age-matched controls (p=0.101). However, during the final half of forced wakefulness, concussed subjects did have more entries into N2 sleep than age-matched controls (p<0.05). Our findings revealed that there was no significant difference in the accumulation and dissipation of sleep pressure between concussed and non-concussed patients. Conclusion: This one of the first studies to acutely sleep-deprive concussed volunteers for longer than 24 h. Even so, these results reject a long-standing assumption that all dynamics of the sleep homeostatic system are residually impacted by mTBI. Support (If Any): Department of Defense Military Operational Medicine Program (MOMRP).